Preparatory phase for clinical trials of COVID-19 vaccine in Nepal - Govind Prasad Gupta; Yogendra Shah; Dhan Kumar Pant; Sunil Lekhak; Ramesh Shahi; Ananda Mandal; Pramod Poudel; Shayam Prakash Dumre; Kishor Pandey; Basu Dev Pandey (Taylor & Francis Group, 2021)
Public health data suggested a rapid rise in COVID-19-confirmed cases in Nepal along with increased deaths. There has been a wide variation in clinical outcomes of this disease. Control of this pandemic depends on the availability of vaccines or drugs for SARS-CoV-2. Thus, viral and human genetics/genomics and immunology are necessary to understand whether these factors will affect clinical trials of vaccines in Nepal.